To Put on the Ethical Glasses – Asking How to Support Ethical Judging in Geography Lessons - Ulrich-Riedhammer, Eva Marie (Journal of Geography Education, 2018)
The aim of the article is to develop a concept which supports ethical judging in Geography lessons. This will be achieved by looking at empirical data. The article continues therefore a doctor thesis about ethical judging in Geography lessons, by focussing on the explicit ethical questions of the pupils in this study. Concerning these ethical questions, the article talks first about how and why one can and has to keep on to these questions in lessons of Geography. This will be done not without discussing the definition of ethical judging in Geography lessons. One further thing to ask is, if ethical theory or the knowledge of certain ethical terms are important to help the pupils answering their questions. From this point a concept of ethical judging will be developed which can be divided into steps of judging and which considers the problem that Geography lessons are not ethic lessons. The steps of this concept, called "ethical glasses", will be concretized, so that they can be applied. These steps can be referred to different ages in school and to different learning stages in one group of learning. The empirical method, which is used, is the so called "dokumentarische Methode". This method makes it possible to analyse explicit and implicit ethical judging. This article is zooming into explicit ethical judging but using the implicit level to explain and justify the developed concept to a greater extent.